Infrared Photon Pair-Production in Ligand-Sensitized Lanthanide Nanocrystals - Agbo, Peter; Kanady, Jacob S.; Abergel, Rebecca J. (Frontiers in Chemistry, 2020)
This report details spectroscopic characterizations of rare-earth, core-shell nanoparticles decorated with the f-element chelator 3,4,3-LI(1,2-HOPO). Evidence of photon downconversion is corroborated through detailed power dependence measurements, which suggest two-photon decay paths are active in these materials, albeit only representing a minority contribution of the sum luminescence, with emission being dominated by normal, Stokes’ shifted fluorescence. Specifically, ultraviolet ligand photosensitization of Nd3+ ions in a NaGdF4 host shell results in energy transfer to a Nd3+/Yb3+-doped NaGdF4 nanoparticle core. The population and subsequent decay of core, Yb3+ 2F5/2 states result in a spectral shift of 620 nm, manifested in a NIR emission displaying luminescence profiles diagnostic of Yb3+ and Nd3+ excited state decays. Emphasis is placed on the generality of this material architecture for realizing ligand-pumped, multi-photon downconversion, with the Nd3+/Yb3+ system presented here functioning as a working prototype for a design principle that may be readily extended to other lanthanide pairs.